Energy efficient modeling and optimization for assembly sequence planning using moth flame optimization - Abdullah, Arif; M. F. F., Ab Rashid; Ponnambalam, S. G.; Zakri, Ghazalli (Emerald Publishing Limited, 2019)
Purpose Environmental problems in manufacturing industries are a global issue owing to severe lack fossil resources. In assembly sequence planning (ASP), the research effort mainly aims to improve profit and human-related factors, but it still lacks in the consideration of the environmental issue. This paper aims to present an energy-efficient model for the ASP problem.